2003
DOI: 10.1002/da.10083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and relationship to delusions and hallucinations of anxiety disorders in schizophrenia

Abstract: We investigated the prevalence of anxiety disorders in a sample of individuals with chronic schizophrenia, controlling for anxiety symptoms that may be related to delusions and hallucinations, and the possible differences in clinical variables between the groups. Individuals with a diagnosis of schizophrenia and able to give informed consent were recruited from the community. The Mini International Neuropsychiatric Interview (MINI) was administered to both confirm the DSM-IV diagnosis of schizophrenia and scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 23 publications
3
52
0
Order By: Relevance
“…Unfortunately, anxiety conditions were not specifically addressed in that study [15]. Finally it has been reported that subjects with paranoid schizophrenia are more likely to suffer panic [16] and social anxiety even when controlling for hallucination and delusion related anxiety [17]. This was indirectly confirmed in our previous study [11], but interestingly JHS was also associated to higher PANSS-P scores.…”
Section: Discusionsupporting
confidence: 63%
“…Unfortunately, anxiety conditions were not specifically addressed in that study [15]. Finally it has been reported that subjects with paranoid schizophrenia are more likely to suffer panic [16] and social anxiety even when controlling for hallucination and delusion related anxiety [17]. This was indirectly confirmed in our previous study [11], but interestingly JHS was also associated to higher PANSS-P scores.…”
Section: Discusionsupporting
confidence: 63%
“…This task-dependent anxiolytic phenotype suggests an impact of Nrg1 on certain explorative/locomotive aspects of anxiety (Rodgers 1997;Rodgers and Johnson 1995). Importantly, anxiety symptoms (and high autonomic arousal) are very variable accompaniments to schizophrenia-often schizophrenia patients are diagnosed with more than one anxiety disorder (Braga et al 2005;Tibbo et al 2003;Townsend and Wilson 2005). Obviously, any animal model for candidate genes of schizophrenia models only some, but not all, aspects of the mental disorder.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies reported no significant influence of gender on the rate of anxiety disorders [30,34,40,44,45,[47][48][49][50][51]. Variation in prevalence rates among different psychiatric disorders was nicely shown by two similar, methodologically Table 4 27.5% had at least one additional anxiety disorder sound studies [36,38].…”
Section: Prevalence Ratesmentioning
confidence: 94%